Adaptation processes in Halomicronema hongdechloris, an example of the light-induced optimization of the photosynthetic apparatus on hierarchical time scales - Schmitt, Franz-Josef; Friedrich, Thomas (Frontiers in Plant Science, 2024)
Oxygenic photosynthesis in Halomicronema hongdechloris, one of a series of cyanobacteria producing red-shifted Chl f, is adapted to varying light conditions by a range of diverse processes acting over largely different time scales. Acclimation to far-red light (FRL) above 700 nm over several days is mirrored by reversible changes in the Chl f content. In several cyanobacteria that undergo FRL photoacclimation, Chl d and/or Chl f are directly involved in excitation energy transfer in the antenna system, form the primary donor in PSI, but are also involved in electron transfer within PSII, most probably at the ChlD1 position, with efficient charge transfer happening with comparable kinetics to reaction centers containing Chl a. In H. hongdechloris, the formation of Chl f under FRL comes along with slow adaptive proteomic shifts like the rebuilding of the D1 complex on the time scale of days. On shorter timescales, much faster adaptation mechanisms exist involving the phycobilisomes (PBS), which mainly contain allophycocyanin upon adaptation to FRL. Short illumination with white, blue, or red light leads to reactive oxygen species-driven mobilization of the PBS on the time scale of seconds, in effect recoupling the PBS with Chl f-containing PSII to re-establish efficient excitation energy transfer within minutes. In summary, H. hongdechloris reorganizes PSII to act as a molecular heat pump lifting excited states from Chl f to Chl a on the ps time scale in combination with a light-driven PBS reorganization acting on the time scale of seconds to minutes dependent on the actual light conditions. Thus, structure-function relationships in photosynthetic energy and electron transport in H. hongdechloris including long-term adaptation processes cover 10-12 to 106 seconds, i.e. 18 orders of magnitude in time.